Comparison of Two Methods in Labor Induction in Nulliparous Women with Unfavorable Cervix at Term: Oxytocin Alone Versus Dinoprostone Vaginal Slow-Release System (Propess®) + Oxytocin - Canda, Tunç; Demir, Namık; Sezer, Orçun (Gynecology Obstetrics & Reproductive Medicine, 2010)
OBJECTIVES: To investigate the efficacy of two labor induction protocols. STUDY DESIGN: In this retrospective study, pregnancy records of 50 nulliparous singletons at term with intact membranes and Bishop score ≤ 6, delivered vaginally with one of the two induction methods were reviewed. Subjects were divided into 2 groups. Group 1; labor induction with oxytocin alone (n=20), Group 2; labor induction with dinoprostone + oxytocin (n=30). RESULTS: Maternal age, time of amniotomy, labor induction to active labor interval, birth weights, pre and post-labor hemoglobin levels and uterine hyperactivity did not show any statistical difference between groups. Oxytocin use was significantly lower and labor induction to delivery interval was found statistically shorter in group 2 (p< 0.05). CONCLUSIONS: The use of dinoprostone vaginal slow-release system plus oxytocin for labor induction in nulliparous women with unfavorable cervix at term seems to be more effective than oxytocin alone.